PERSEPSI MASYARAKAT SURABAYA DALAM PENGGUNAAN E-WALLET DANA - Tandany, Maria Yuliana Elisabeth (Universitas Widya Kartika Surabaya, 2024)
Surabaya Community Perceptions in Using Dana E-wallet. A person's perception is the process of selecting, interpreting information or an object received through sight, taste, hearing, smell and touch which can provide different viewpoints in sensing, both positive and negative perceptions which will influence visible or real human actions. This research aims to study the perception of the people of Surabaya regarding the use of the Dana E-wallet in this modern era with a lot of competition from digital wallet platforms that continue to develop. The number of sources used in this research was 6 sources using descriptive qualitative data analysis methods. The research results prove that the perception of the people of Surabaya for each individual is formed from need factors, age factors, and also lifestyle factors. The formation of the need factor is based on the easy automatic action of the e-wallet so that there is an age factor that helps parents fulfill their needs. Lifestyle factors are formed based on a person's lifestyle in the modern era when everything is easy, aided by increasing technology. So that in the end it increases public trust in the security system provided by Dana and provides loyalty and loyalty from users to Dana's E-wallet.